Controlled Synthesis of Core–Shell Carbon@MoS2 Nanotube Sponges as High‐Performance Battery Electrodes. Issue 46 (30th September 2016) - Wang, Yunsong; Ma, Zhimin; Chen, Yijun; Zou, Mingchu; Yousaf, Muhammad; Yang, Yanbing; Yang, Liusi; Cao, Anyuan; Han, Ray P. S.
Abstract : Heterogeneous inorganic nanotube structures consisting of multiwalled carbon nanotubes coated by long, continuous MoS2 sheets with tunable sheet number are synthesized using a carbon‐nanotube sponge as a template. The resulting 3D porous hybrid sponges have potential applications as high‐performance freestanding anodes for Li‐ion batteries with excellent specific capacity and cycling stability.